THE CHRISTIAN PARADIGM ON THE ESSENCE AND EXISTENCE OF CHARACTER IN EDUCATION - Marde Christian Stenly Mawikere; Sudiria Hura; Jean Calvin Riedel Mawikere; Daniella Beauty Melanesia Mawikere (Didaskalia: Jurnal Pendidikan Agama Kristen, 2024)
This article examines the Christian paradigm concerning the essence and existence of character in education, focusing on the transformation of learning from the Renaissance era to the 21st century. The study reveals philosophical reflections on contemporary education, the role of educators as parental figures in shaping students' character, and the qualifications of an educator’s character from a Biblical perspective. The research methodology involves a study of Biblical texts and a qualitative content analysis approach applied to relevant literature. The findings underscore the importance of the life example, service, and teachings of Jesus Christ in shaping character aligned with Christian values in education. Educators are expected to apply ethics and morals in teaching to guide students in becoming individuals who are not only intellectually capable but also morally responsible and dedicated to serving society. This study offers practical guidance for educators in integrating Christian values into the educational process.